ANALISIS KUALITAS PELAYANAN DI BALAI KESEHATAN INDERA MASYARAKAT (BKIM SEMARANG) - Diar, Ailsa Rachma; Nurcahyanto, Herbasuki; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2015)
The quality of public health services is an activity which is provided by public service providers to fill the needs and expectations of the community health. Balai Kesehatan Indera Masyarakat (BKIM) Semarang is a public organization that operates in the field of health care specialists. The aim of the research are to assess the quality of health services in BKIM Semarang and to identify the dimensions that hamper the quality of health services in BKIM Semarang. the dimensions that used to measure the service’s quality provided by BKIM Semarang consist of tangible, reliability, responsiveness, assurance and emphaty. The result of this research showed that the quality of health services organized by BKIM Semarang can be said less good because there are many deficient in service process. This was evidenced by the facilities such as parking area and information board are still inadequate, long service time, undicipline employees, and disclosure of public’s information remains low. The dimensions that need to be improved in order to increase service quality are tangible, reliabilty and empathy because there still have some lacks. The efforts to improve service quality can be done by adding the quantity of facilities and infrastructure, managing the parking area, recruting health’s experts, employees development, giving a punishment to improve dicipline, setting a Citizen’s Charter and increasing coordination with Dinas Kesehatan Provinsi Jawa Tengah.